2009
DOI: 10.2134/agronj2008.0144
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Recovered Magnesium Phosphates as Fertilizers in Neutral and Slightly Alkaline Soils

Abstract: A gronomy J our n al • Volume 101, I s sue 2 • 2 0 0 9 323

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 22 publications
10
104
0
4
Order By: Relevance
“…In the Se SSP outperformed struvite, while the reverse was true on the Cf soil and on the Ia no response was observed from either SSP or struvite (Table 3). The inconsistent performance of struvite has been reported before by Ackerman et al (2013) and Massey et al (2009) they both concluded that struvite effectiveness as a P fertilizer is dependent on soil properties. This proposition is in agreement with the results obtained on this study.…”
Section: Discussionmentioning
confidence: 79%
“…In the Se SSP outperformed struvite, while the reverse was true on the Cf soil and on the Ia no response was observed from either SSP or struvite (Table 3). The inconsistent performance of struvite has been reported before by Ackerman et al (2013) and Massey et al (2009) they both concluded that struvite effectiveness as a P fertilizer is dependent on soil properties. This proposition is in agreement with the results obtained on this study.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies comparing P fertilizers/struvites recovered from various materials to commercial P fertilizer have reported that the recycled products increased DMY in maize [20], led to comparable DMY in perennial ryegrass [22], or at least improved DMY compared to untreated controls in several crops [17][18][19]43].…”
Section: The Fertilizing Performance Of P-salt Is Equivalent To That mentioning
confidence: 98%
“…A few reports of the comparison of soils with different pH values can be found in previous research. 10,13 Cabeza et al 10 studied the effectiveness of struvite as fertilizer compared with superphosphate and phosphate rock in a 2-year pot experiment with maize in two soils with contrasting pH (4.7 and 6.6) and concluded that struvite was as effective as superphosphate in both soils.…”
Section: ■ Introductionmentioning
confidence: 99%